Experimental Investigation for Tensile Performance of GFRP-Steel Hybridized Rebar. (21st February 2016) - Seo, Dong-Woo; Park, Ki-Tae; You, Young-Jun; Lee, Sang-Yoon
Abstract : Tensile performance of the recently developed "FRP Hybrid Bar" at Korea Institute of Civil Engineering and Building Technology (KICT) is experimentally evaluated by the authors. FRP Hybrid Bar is introduced to overcome the low elastic modulus of the existing GFRP bars to be used as a structural member in reinforced concrete structures. The concept of material hybridization is applied to increase elastic modulus of GFRP bars by using steel. This hybridized GFRP bar can be used in concrete structures as a flexural reinforcement with a sufficient level of elastic modulus. In order to verify the effect of material hybridization on tensile properties, tensile tests are conducted. The test results for both FRP Hybrid Bar and the existing GFRP bars are compared. The results indicate that the elastic modulus of FRP Hybrid Bar can be enhanced by up to approximately 250 percent by the material hybridization with a sufficient tensile strength. To ensure the long-term durability of FRP Hybrid Bar to corrosion resistance, the individual and combined effects of environmental conditions on FRP Hybrid Bar itself as well as on the interface between rebar and concrete are currently under investigation.